Paper 08: Outcomes After Arthroscopic Pancapsular Shift for the Treatment of Multidirectional Glenohumeral Instability at a Mean 9 Year Follow-up. Issue 7 (30th July 2022) - Rakowski, Dylan; Woolson, Thomas; Horan, Marilee; Millett, Peter; Gruskay, Jordan
Objectives: Arthroscopic treatment with suture anchors of multidirectional instability (MDI) of the shoulder is gaining popularity as compared to an open approach, but no studies with mid to long-term outcomes are reported in the literature. Meanwhile, atraumatic onset MDI is associated with worse outcomes compared to traumatic onset MDI in short-term studies. The objective of this study is to report on survivorship and patient reported outcomes following arthroscopic pancapsular shift (APS) for MDI with minimum five-year follow up, including comparing atraumatic versus traumatic onset MDI. Methods: Patients who underwent APS for MDI and were at a minimum 5 years postoperative from the surgical intervention were included. Baseline pre and perioperative data was prospectively collected as part of an institutional registry and retrospectively reviewed, and patient questionnaires were sent by email to determine long-term outcomes including mechanism of onset of MDI, patient satisfaction, Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH), American Shoulder and Elbow Surgeons (ASES), Short Form-12 Physical Component Summary (SF-12 PCS), and Single Assessment Numeric Evaluation (SANE) scores. Additional information about recurrent instability, dislocation and reoperation as well as return to sport were collected and Kaplan-Meier survivorship analysis was performed. Preoperative, short-term (1-2 year) and final follow-up patient reported outcomes were compared. Results: 49 shoulders in 44 patients (15 male, 29 female) treated between October 2005 and November 2015 were included in the study. Overall, 14/49 (28.6%) of shoulders reported feelings of instability, of which 5 (10.2%) underwent revision surgery at a mean of 1.5 years postoperatively. Kaplan-Meier analysis demonstrated a survivorship rate of 80% at 5 years and 75% at 8 years with failure defined at postoperative feelings of instability. Final analysis was performed on 44 shoulders, of which minimum 5-year outcomes were collected on 36 (82%) with an average follow-up length of 9.0 years (5.1-14.6 years). All patient reported outcome scores as well as subjective improvement outcomes demonstrated statistically significantly improved results at final follow-up (p<0.05). Patient reported outcome measures were persistently statistically significantly improved at short-term and long-term final follow-up. (Figure 1) MDI onset was atraumatic in 27 shoulders and traumatic in 21. There was no difference in subjective or patient reported outcome scores between atraumatic and traumatic onset MDI patients. Rotator interval closure was performed in 19 patients with no effect on postoperative outcomes. Conclusions: Arthroscopic pancapsular shift for the treatment of MDI provides excellent, durable long-term patient reported outcomes that persist from short-term follow-up. Although 28% of patients experience feelings of instability at final follow-up, most of these patients still have high postoperative satisfaction and acceptable patient reported outcomes and do not undergo revision surgery Compared to short-term data, long-term results indicate that atraumatic onset MDI is not associated with worsened postoperative outcomes as compared to traumatic onset MDI.